The Academic Stress Coping Scale for High School Students - Putu Febry Shaputra; Kadek Suranata (Bisma The Journal of Counseling, 2023)
Changes in learning needs, especially High pressure to achieve learning outcomes is a key reason for stress in high school students.This research aims to develop an academic stress coping scale for high school students and to analyze the stress coping possessed by high school students. This research is an R&D development research with subjects of 63 class XI high school students who have high academic stress. The action involved administering two types of questionnaires: the academic stress coping questionnaire and the DAS-21 questionnaire, then collecting the data on a questionnaire sheet given to students. The collected academic stress coping data was then analyzed using descriptive analysis techniques. The results of the research show that the academic stress coping scale developed has a weak positive correlation with the Distress Anxiety Scale-21 (DAS-21) questionnaire with concurrent test results of 0.179 with an F-table value of 0.05 (5%) N = 63 – 1 = 62, the F-table value is 1.998, so the F-count < F-table. The DAS-21 questionnaire, when used with the academic stress coping questionnaire, is invalid. It cannot adequately measure students' academic stress, necessitating the use of a dedicated academic stress coping questionnaire to accurately assess and explore students' stress levels. It can be concluded that the development of the academic stress coping scale questionnaire was successful and can be used to measure student academic stress. The innovation in this research has implications for handling stress experienced by students more optimally.